Open and distance learning: a bibliometric analysis using scopus database and vosviewer - Supriyadi, Edi; Bonyah, Ebenezer (Polyhedron International Journal in Mathematics Education, 2023)
This study presents a bibliometric analysis of open and distance learning (ODL) literature to explore the impact of new technologies, temporal trends in research, and the influence of open pedagogy and educational resources on learner engagement and inclusion. Utilizing Scopus as the primary data source for its comprehensive coverage and analytical capabilities, a dataset was curated using specific keywords and analyzed through VosViewer. The results demonstrate a significant increase in ODL publications, indicative of growing scholarly interest and a diverse, global research community. Key findings reveal a network of influential institutions and scholars central to ODL, with highly cited documents highlighting foundational research and prevalent themes. The analysis underscores the importance of technological, pedagogical, strategic, and evaluative themes, signifying the complex and interdisciplinary nature of ODL. Suggestions for future research include qualitative analyses to understand ODL's progression and longitudinal studies to gauge the influence of global events on ODL practices. Collaborative and cross-disciplinary efforts are encouraged to innovate educational modalities. The study’s implications reflect ODL's growing relevance in educational policy and practice, the influence of key scholars and institutions in shaping ODL discourse, and the strategic research focus that may dictate future educational developments. This analysis charts the trajectory of ODL, contributing to its strategic evolution and enduring relevance in education.